2017
DOI: 10.1016/j.pedneo.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Self-Report Pubertal Timing and Menarcheal Age on Adolescent Psychological and Behavioral Outcomes in Female Youths from Northern Taiwan

Abstract: Conceptual and actual pubertal developments may be differentially associated with psychobehavioral outcomes among young Taiwanese girls. Clinical attention should be given to adolescent self-perception of sexual maturation and developmental guidance provided accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
0
22
1
Order By: Relevance
“…Other researchers have evidenced only early maturation to influence psychological adjustment Ge et al, 2001;Ge et al, 2006;Graber et al, 2006;Negriff et al, 2015Negriff et al, , 2010Negriff et al, , 2009Negriff et al, , 2008Stice et al, 2001). Similarly, Lee et al (2017) in their work found only early-maturing girls based on PDS having higher rates of smoking and sexual activity. However, this influence of early pubertal timing also tends to differ across gender like Strong et al (2016) in their study found effect of early pubertal timing on adolescent's depression only in males but not in females.…”
Section: Pubertal Timing and Gender Differences In Problem Behavioursmentioning
confidence: 87%
“…Other researchers have evidenced only early maturation to influence psychological adjustment Ge et al, 2001;Ge et al, 2006;Graber et al, 2006;Negriff et al, 2015Negriff et al, , 2010Negriff et al, , 2009Negriff et al, , 2008Stice et al, 2001). Similarly, Lee et al (2017) in their work found only early-maturing girls based on PDS having higher rates of smoking and sexual activity. However, this influence of early pubertal timing also tends to differ across gender like Strong et al (2016) in their study found effect of early pubertal timing on adolescent's depression only in males but not in females.…”
Section: Pubertal Timing and Gender Differences In Problem Behavioursmentioning
confidence: 87%
“…This was, however, inconsistent with those with measurements using perceived maturity in comparison with peers [ 21 ]. The explanation is that interpretations of perceived maturity likely vary according to personal perceptions that are formulated through the experiences of peer comparisons [ 22 ]. For example, viewing pornography could be regarded as a sign of maturity, hence a normative behavior among male peers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 Lin et al (1992 use the 1985 round; Ohsawa, Ji and Kasai (1997) base their results on the 1991 round. 41 Chan et al 2009, 20;Lee et al 2017, 316. 42 Papadimitriou 2016.…”
Section: Notementioning
confidence: 99%